1986
DOI: 10.1148/radiology.160.1.2940618
|View full text |Cite
|
Sign up to set email alerts
|

Paget disease of the spine: CT with clinical correlation.

Abstract: Thirty-six patients with pagetic involvement of the spine were evaluated clinically and by computed tomography (CT). Pagetic phase, modeling expansion, degree and site of spinal stenosis, and pagetic facet joint arthropathy were recorded for each involved vertebral segment. CT demonstrated spinal stenosis in 20 patients, 11 of whom exhibited spinal stenosis on plain films. Twenty-one patients had symptoms of neck or back pain, with associated neurologic dysfunction in 13. Spinal stenosis was present in 81% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 0 publications
1
32
0
1
Order By: Relevance
“…Back pain in PD may also be attributed to blood engorgement of the vertebral body caused by vascular and disorganized, hyperactive remodeling processes [90]. Other factors implicated in spinal pain may include invasion of the vertebral disc space by the pagetic process [90], and spinal stenosis [170]. We hypothesize that microfractures of the pagetic vertebral bodies, especially in the osteolytic or mixed phase, can also lead to back pain [66].…”
Section: Spinal Stenosismentioning
confidence: 98%
See 2 more Smart Citations
“…Back pain in PD may also be attributed to blood engorgement of the vertebral body caused by vascular and disorganized, hyperactive remodeling processes [90]. Other factors implicated in spinal pain may include invasion of the vertebral disc space by the pagetic process [90], and spinal stenosis [170]. We hypothesize that microfractures of the pagetic vertebral bodies, especially in the osteolytic or mixed phase, can also lead to back pain [66].…”
Section: Spinal Stenosismentioning
confidence: 98%
“…The spine is the second most commonly affected site in PD [4,33,82,105], predisposing patients to low back pain and spinal stenosis [6,72,76,170]. Hartman and Dohn [74] have shown that 15.2% of patients with PD had involvement of the vertebrae, and 26% of these patients had symptoms of spinal stenosis.…”
Section: Prevalence Of Back Pain and Spinal Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…The spine is the second most commonly affected site in PD [2,30,95], predisposing patients to low back pain and spinal stenosis [4,52,64,137]. Hartman and Dohn have shown that 15.2% of patients with PD had involvement of the vertebrae, and 26% of these patients had symptoms of spinal stenosis [59].…”
Section: Prevalence Of Back Pain and Spinal Stenosismentioning
confidence: 99%
“…15) [80], and spinal stenosis [137]. The authors hypothesize that microfractures of pagetic vertebral bodies, especially in the osteolytic or mixed phase, can also lead to back pain [46].…”
Section: Spinal Pain (Back Pain and Neck Pain)mentioning
confidence: 99%